1998
DOI: 10.1002/(sici)1097-4628(19980207)67:6<1093::aid-app17>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Studies on jute-reinforced composites, its limitations, and some solutions through chemical modifications of fibers

Abstract: Jute, unlike other natural fibers, absorbs moisture and its moisture regain property is quite high. Water migration and subsequent degradation of jute-based composites can be a problem. Because jute is hydrophilic and the matrix resins are mostly hydrophobic, wetting of the fibers with resins is poor, for which high resin consumption may occur that would increase the cost of composites. To reduce the moisture regain property of jute fiber, it is essential to pretreat the jute fiber so that the moisture absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 0 publications
0
58
0
Order By: Relevance
“…These structures contain reactive functional groups that are capable of bonding to the reactive groups in the matrix polymer. Thus modification of natural fibers is attempted to make the fiber hydrophobic and to improve interfacial adhesion between the fiber and the matrix polymer [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] . Chemical treatment of natural fibers has been reviewed where it reported 58 that such as de-waxing (de-fatting), de-lignifications, bleaching, acetylation, cynoethylation 72 , and chemical grafting were used for modifying the surface properties of the fibers for enhancing its performance.…”
Section: Modification Of Natural Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…These structures contain reactive functional groups that are capable of bonding to the reactive groups in the matrix polymer. Thus modification of natural fibers is attempted to make the fiber hydrophobic and to improve interfacial adhesion between the fiber and the matrix polymer [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] . Chemical treatment of natural fibers has been reviewed where it reported 58 that such as de-waxing (de-fatting), de-lignifications, bleaching, acetylation, cynoethylation 72 , and chemical grafting were used for modifying the surface properties of the fibers for enhancing its performance.…”
Section: Modification Of Natural Fibersmentioning
confidence: 99%
“…The treatment resulted in an increase in de-bonding stress and thus improved the ultimate tensile strength up to 30%. Basak 71 , et al have reported that treatment of jute with poly-condensates such as phenol-formaldehyde, melamine-formaldehyde, and cashew nut shell liquid-formaldehyde improved the wettavbility of jute fibers and reduced the water regain properties. Treatment with cardanol-formaldehyde was also found to reduce water absorption and improved the mechanical properties of jute/polypropylene composite 73 material.…”
Section: Modification Of Natural Fibersmentioning
confidence: 99%
“…Various fibre surface treatments have been reported, such as: alkali [4][5][6][7][8], silane [9][10][11][12][13], combination of alkali and silane [14,15], monomer grafting under UV radiation [16][17][18], maleic anhydride grafted polypropylene [19][20][21][22], and others [23][24][25][26][27][28]. Among those commercial coupling agent maleic anhydride grafted polypropylene (MAHgPP) has been found to be the most efficient in improving interfacial adhesion of natural fibres and a PP matrix [29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The details of these procedures are described in the following paragraphs. PF resins (melamine formaldehyde, cashew nut shell liquid-formaldehyde, and polymerized cashew nut shell liquid) when applied on jute felt led to enhanced tensile strength and water repellence of composites manufactured from treated felt [80]. Decreased water uptake is attributed to cross-linking of LCFs and resin matrix through hydrogen bonds and subsequent development of weakly bonded networks connected through secondary bonds (Scheme 11a).…”
Section: Coating or Blockingmentioning
confidence: 99%